(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Conventional trauma models often prioritize symptom reduction over restoring personal identity and narrative coherence, a critical gap for displaced and cross-cultural populations. This study proposes and tests the Internal Autobiographical Map (IAM), a framework for organizing life stories to foster resilience. A mixed-methods approach was utilized a structured questionnaire with 384 trauma-affected individuals from diverse backgrounds. Quantitative analyses revealed a strong positive association between autobiographical mapping and psychological resilience (r up to .764, p < .001). Factor analysis confirmed IAM as a robust, unidimensional construct explaining 88.46% of the variance. Storytelling (β = .508, p < .001) and positive reframing (β = .362, p = .005) were significant resilience predictors. Individuals with trauma histories scored significantly higher on IAM engagement (p < .001), indicating its role in identity reconstruction. The IAM is a powerful, culturally adaptable tool that empowers individuals to rebuild a coherent identity, thereby enhancing psychological resilience and enabling sustainable recovery that transcends clinical and cultural boundaries.